Preventing the next pandemic: Zoonotic diseases and how to break the chain of transmission - United Nations Environment Programme; International Livestock Research Institute (2020)
In the spirit of the UN Framework for the Immediate Socio-economic Response to COVID-19, the United Nations Environment Programme (UNEP) has teamed up with the renowned International Livestock Research Institute (ILRI) and other key partners to develop an evidence-based assessment report on the risk of future zoonotic outbreaks. This report focuses specifically on the environmental side of the zoonotic dimension of disease outbreaks during the COVID-19 pandemic. It tries to fill a critical knowledge gap and provide policymakers with a better understanding of the context and nature of potential future zoonotic disease outbreaks. It examines the root causes of the COVID-19 pandemic and other zoonoses. The report also looks at where zoonoses come from and how we can reduce the likelihood of their occurrence. The report explores the role of animals, and in particular non-domestic animals, in emerging infectious human diseases. This is essential for our global efforts to improve our response preparedness because the frequency of spillover of pathogenic organisms jumping from animals to humans has been increasing considerably, due to the growing magnitude of our unsustainable natural resource use in today’s world.